Worse patient-physician relationship is associated with more fear of cancer recurrence (Deimos Study): A study of the Palliative Care Working Committee of the Turkish Oncology Group (TOG) - YUMUK, PERRAN FULDEN; BAŞOĞLU TÜYLÜ, TUĞBA (WILEY, 2020)
Objective Fear of cancer recurrence (FCR) is an important psychological trauma associated with reduction in the quality of life, disruptions in the level of adjustment, emotional distress and anxiety. The purpose of the study was to evaluate the impact of patient-physician relationship on FCR. Methods The study was designed as a multicentre survey study. The cancer survivors, who were under remission, were evaluated with structured questionnaires. Patient-physician relationship (PPR) scale in which higher scores indicate better relationship and FCR inventory was used. Results Between January and April 2019, 1,580 patients were evaluated. The median age was 57.0 (19-88), and 66% were female. There was high level of FCR scores in 51% of participants. There was a negative correlation between PPR and FCR scores (r = -.134,p < .001). In multivariate analysis, young age, female gender, history of metastasectomy and worse PPR were associated with high levels of FCR. Conclusion It is the first data showing the adverse impact of worse PPR on FCR. The strategies to improve the PPR should be practised. In addition, the cancer survivors, who are under the risk of FCR, should be evaluated and managed.
Keywords: fear of cancer recurrence; oncology; patient-physician relationship; survivor; QUALITY-OF-LIFE; AFRICAN-AMERICAN; SURVIVORS; BREAST; TRUST; WOMEN; TIME